If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -7)(x) = 120 Reorder the terms: (-7 + 3x)(x) = 120 Reorder the terms for easier multiplication: x(-7 + 3x) = 120 (-7 * x + 3x * x) = 120 (-7x + 3x2) = 120 Solving -7x + 3x2 = 120 Solving for variable 'x'. Reorder the terms: -120 + -7x + 3x2 = 120 + -120 Combine like terms: 120 + -120 = 0 -120 + -7x + 3x2 = 0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. -40 + -2.333333333x + x2 = 0 Move the constant term to the right: Add '40' to each side of the equation. -40 + -2.333333333x + 40 + x2 = 0 + 40 Reorder the terms: -40 + 40 + -2.333333333x + x2 = 0 + 40 Combine like terms: -40 + 40 = 0 0 + -2.333333333x + x2 = 0 + 40 -2.333333333x + x2 = 0 + 40 Combine like terms: 0 + 40 = 40 -2.333333333x + x2 = 40 The x term is -2.333333333x. Take half its coefficient (-1.166666667). Square it (1.361111112) and add it to both sides. Add '1.361111112' to each side of the equation. -2.333333333x + 1.361111112 + x2 = 40 + 1.361111112 Reorder the terms: 1.361111112 + -2.333333333x + x2 = 40 + 1.361111112 Combine like terms: 40 + 1.361111112 = 41.361111112 1.361111112 + -2.333333333x + x2 = 41.361111112 Factor a perfect square on the left side: (x + -1.166666667)(x + -1.166666667) = 41.361111112 Calculate the square root of the right side: 6.431260461 Break this problem into two subproblems by setting (x + -1.166666667) equal to 6.431260461 and -6.431260461.Subproblem 1
x + -1.166666667 = 6.431260461 Simplifying x + -1.166666667 = 6.431260461 Reorder the terms: -1.166666667 + x = 6.431260461 Solving -1.166666667 + x = 6.431260461 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.166666667' to each side of the equation. -1.166666667 + 1.166666667 + x = 6.431260461 + 1.166666667 Combine like terms: -1.166666667 + 1.166666667 = 0.000000000 0.000000000 + x = 6.431260461 + 1.166666667 x = 6.431260461 + 1.166666667 Combine like terms: 6.431260461 + 1.166666667 = 7.597927128 x = 7.597927128 Simplifying x = 7.597927128Subproblem 2
x + -1.166666667 = -6.431260461 Simplifying x + -1.166666667 = -6.431260461 Reorder the terms: -1.166666667 + x = -6.431260461 Solving -1.166666667 + x = -6.431260461 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.166666667' to each side of the equation. -1.166666667 + 1.166666667 + x = -6.431260461 + 1.166666667 Combine like terms: -1.166666667 + 1.166666667 = 0.000000000 0.000000000 + x = -6.431260461 + 1.166666667 x = -6.431260461 + 1.166666667 Combine like terms: -6.431260461 + 1.166666667 = -5.264593794 x = -5.264593794 Simplifying x = -5.264593794Solution
The solution to the problem is based on the solutions from the subproblems. x = {7.597927128, -5.264593794}
| 3x+9y=27solvey | | 11.2=v/7 | | 10x-12x=20 | | 17v=9v+48 | | x^3-10x^2+17x-8=0 | | 4x-7=2y+5 | | 15x+10=6x+298 | | -5-15y+1=2(7y-16)-y | | X-1/6=7/12 | | 10x-12x-8=12 | | 3x-2=2x(-6) | | -114q=-1176-16q | | A=18W-W^2 | | ix-3x=0 | | 2(x-4)=3x-9-x | | y-2=4/5(x-3) | | (2x-1)(5x-5)= | | 4r-4=(r-4)(r-4) | | 0.6x-1.9y+3.2=0 | | 160=3x+y | | -9y+19=4y-7 | | 1-4.9x^2=0 | | (w-4)/4w=1/5 | | 12y-7+1+4y= | | ix=3x | | 7-2y=10-6y+4y | | x(x-3)=16/3 | | -3(5u-2)+5u=4(u+4) | | 3(4y)=24 | | 6(x-3)=9x-24 | | 2(6d+3)=18-48+9d | | X+(x-5)=20 |